Penerimaan Anak Terhadap Poligami Ayahnya di Balikpapan - Paryadi Paryadi (LPPM STIS Hidayatullah, 2021)
Polygamy can have a psychological and sociological impact, both on wives and children. This study focuses on the acceptance of children to their father's polygamy. Researchers used a qualitative approach by selecting case studies. Research with case studies, looks at a problem or case from many data sources. It is hoped that the data will reveal the responses of four respondents in Balikpapan to their father's polygamy. The results showed that the respondents had no direct or indirect rejection. It is evident from the maintained communication relationship with his father, mother and new mother. But according to the other side, the four respondents were very careful in their behavior, so that something was played out so as not to disappoint their father and mother.